A wheat CC-NBS-LRR protein Ym1 confers WYMV resistance by recognizing viral coat protein - Yiming Chen; Dehui Kong; Zongkuan Wang; Jiaqian Liu; Linghan Wang; Keli Dai; Jialun Ji; Wei Chen; Xiong Tang; Mingxing Wen; Xu Zhang; Huajian Zhang; et al. (Nature Communications)
Abstract Ym1 is the most widely utilized gene for wheat yellow mosaic virus (WYMV) disease control in worldwide wheat breeding. Here, we successfully isolated the responsible gene for Ym1. It encodes a typical CC-NBS-LRR type R protein, which is specifically expressed in root and induced upon WYMV infection. Ym1-mediated WYMV resistance is likely achieved by blocking viral transmission from the root cortex into steles, thereby preventing systemic movement to aerial tissues. Ym1 CC domain is essential for triggering cell death. Ym1 specifically interacts with WYMV coat protein, and this interaction leads to nucleocytoplasmic redistribution, a process for transitioning Ym1 from an auto-inhibited to an activated state. The activation subsequently elicits hypersensitive responses and establishes WYMV resistance. Ym1 is likely introgressed from the sub-genome Xn or Xc of polyploid Aegilops species. The findings highlight an exogenous-introgressed and root-specifically expressed R gene that confers WYMV resistance by recognizing the viral component.